Producing Appropriation: Negotiating Islam-Sunda in Terebang Sejak - Neneng Yanti Khozanatu Lahpan (International Journal of Nusantara Islam, 2014)
This article is an ethnographic account of my research on negotiating Islam and Sunda in Islamic Sundanese music. By taking special case of Terebang Sejak, I draw my attention on the issue based on my fieldwork in Cikeusal village, TasikMalaya, West Java. Observations and interviews are the main tools I used in gathering information. By presenting particularity of Terebang Sejak, this paper aims to present complexity and negotiations that are formed from the interaction between Islam and Sunda in the music in the village. In this context, presenting the idea of the truism of marginalizing Islam on local culture is in accordance with the idea of Indonesian modernity, which has parallelism with the mission of modernist Islam. While many scholars describe Islam in Indonesia with the idea of syncretism to depict the religion as ‘not really Islam’, in this article I provide different interpretation of localizing Islam by which people produce their own interpretation and appropriation in response to social and political changes in their environs. This interpretation will contribute to new understanding in addressing the particularity of meanings based on local knowledge, among Cikeusal people that forms what coded as ‘identity’ of being Muslim-Sunda. Here, Islamic text of Kitab Mulud in the music has played an agentive role to acknowledge the music as Islamic, thus continues to be part of ritual.